Encyclopedia of American gospel music - McNeil, W. K., 1940-2005 (Routledge, 2005)
The Encyclopedia of American Gospel Music covers all aspects of both African American and white gospel from history and performers to recording techniques and styles, as well as the influence of gospel on different musical genres and cultural trends. Organized alphabetically to facilitate searching, this encyclopedia also contains many reference tools to aid the user, such as bibliographic and references at the end of entries, a thorough and analytical index, and black-and-white illustrations. Entries include biographical profiles of numerous performers, such as Andrae Crouch, and influential figures in the development of gospel music, such as Isaac Watts; important events in the history of gospel such as the Azusa Street Revival; broadcasting outlets, such as radio station WLAC AM, and record companies, such as Canaan Records, that were prominent in gospel's history; publications, such as The Singing News, significant songbooks, such as Gospel Pearls, and noteworthy publishing companies, such as Lillenas, all of which helped popularize some of the best-known gospel songs; and topics ranging from instruments frequently used by gospel performers to types of performing groups, such as gospel quartets and gospel choirs, to the unique qualities of gospel as it is composed and performed in different regions around the United States, to the globalization of gospel. --From publisher's description.